Differences In The Intensity Of Pain During Surgical Wound Treatment Between Patients Using Distraction And Relaxation Techniques At The Derah Gunungsitoli General Hospital In 2020 - Dedi Mizwar Tarihoran; Leli Desi Uli Basana; Ana Ester Lase (Science Midwifery, 2020)
Wound care is an action to prevent infection and accelerate wound healing. But in its implementation can increase the intensity of pain. The results of a preliminary study of 87.5% of the sample stated that the pain increased during wound treatment. To reduce pain, pain management is used both pharmacologically and non-faramacologically. Non-pharmacologically there are various techniques such as stimulus and massage kutaneus, distractions, ice and heat therapy, hypnosis and relaxation. This study aims to prove that there is a difference in pain intensity between using distraction techniques and relaxation during surgical wound treatment. This type of research uses quasi-experiments, the methods used are pre-test and post test graup design. The sample consisted of 30 respondents selected by means of sampling quotas then divided into two, namely 50% received distraction technical treatment and another 50% received relaxation treatment. Data collection is carried out with .